Pendampingan Karakter Menjaga dan Mengurangi Pencemaran Lingkungan Menuju Sustainable Development Goals (SDGs) - Zainuddin M; Suri Handayani Damanik; Silvia Mariah Handayani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Environmental pollution has become one of the crucial problems faced by various countries in the world, including Indonesia. One of the main contributors to environmental pollution is waste, specifically plastic waste, which continues to increase in volume as the population grows and the consumption of modern society. State Elementary School (SDN) 104201 Kolam, as one of the basic education institutions, faces the same challenges in efforts to protect the environment around the school and instill environmental concern values in its students. A clean, healthy, and sustainable school environment not only supports an effective learning process, but also serves as an example for the surrounding community. Therefore, a structured and sustainable character mentoring program is needed to equip SDN 104201 Kolam students with knowledge, attitudes, and skills in maintaining and reducing environmental pollution. This Community Service Activity (PKM) is carried out by solving problems found in partners, namely 1) Lack of behavior to protect the environment and reduce environmental pollution. 2) Not maximized character learning to dispose of garbage to realize educating children in realizing environmentally friendly schools and making a real contribution to the achievement of the SDGs. In solving these problems, several stages have been carried out. The initial stage of mentoring began with education and socialization about the importance of protecting the environment and the dangers of pollution, introducing the concept of 3R (Reduce, Reuse, Recycle) as a basic framework for waste management and the importance of fostering awareness in students about protecting and caring for the environment was emphasized from the beginning. From the results of observations after the service was carried out, it was found that the mentoring program succeeded in shifting the habit of disposing of mixed waste towards organic and inorganic waste sorting, with a significant increase in the volume of sorted waste.